Location privacy preservation approach towards to content sharing on mobile online social network - Chao LI; Li-hua YIN; Kui GENG; Bin-xing FANG (Tongxin xuebao)
A privacy access control model for content sharing was presented to fine-grained control users' location infor-mation associated with sharing content in mobile social network. A k-anonymity privacy algorithm for privacy settings was given to protect against inference attack on a content sharing service provider server. To balance the privacy and quality of service, a location shifting method was presented. Finally experimental results demonstrate the validity and practicality of the proposed approach.